The genus Hylaeus Fabricius in Central Asia (Hymenoptera: Apoidea: Colletidae) - Dathe, Holger H.; Proshchalykin, Maxim Yu. (Zootaxa, 2018)
All presently available information about bees of the genus Hylaeus F. in Central Asia is summarized. Seventy species are currently known from this area. Ten new species are described: Hylaeus gissariensis Dathe & Proshchalykin, sp. nov. (Tajikistan), H. karagandicus Dathe & Proshchalykin, sp. nov. (Kazakhstan), H. kirgisicus Dathe & Proshchalykin, sp. nov. (Kyrgyzstan), H. klausnitzeri Dathe & Proshchalykin, sp. nov. (Kyrgyzstan), H. michaelis Dathe & Proshchalykin, sp. nov. (Kyrgyzstan), H. murgabensis Dathe & Proshchalykin, sp. nov. (Tajikistan), H. pamirensis Dathe & Proshchalykin, sp. nov. (Tajikistan), H. petzi Dathe & Proshchalykin, sp. nov. (Tajikistan), H. piotris Dathe & Proshchalykin, sp. nov. (Uzbekistan, Kyrgyzstan, Turkmenistan, Tajikistan), and H. rushanicus Dathe & Proshchalykin, sp. nov. (Uzbekistan, Tajikistan). In addition, the male of H. punctiventris Morawitz, 1876 is described for the first time.—Twenty species are newly recorded from Central Asia: Hylaeus alexandrinus (Warncke, 1992), H. annulatus (Linnaeus, 1758), H. araxanus (Warncke, 1981), H. brevicornis Nylander, 1852, H. cardioscapus Cockerell, 1924, H. dorni Dathe, 1986, H. gredleri Förster, 1871, H. kozlovi Dathe & Proshchalykin, 2016, H. leleji Proshchalykin & Dathe, 2016, H. lineolatus (Schenck, 1861), H. longimaculus (Alfken, 1936), H. mellon Dathe & Proshchalykin, 2016, H. meridionalis Förster, 1871, H. moricei (Friese, 1898), H. nimbatus Dathe, 1986, H. paulus Bridwell, 1919, H. pesenkoi Proshchalykin & Dathe, 2016, H. rugicollis Morawitz, 1874, H. stubbei Dathe, 1986 and H. tsingtauensis (Strand, 1915).—New synonymy has been established for Hylaeus arenarius Morawitz, 1876 (= Prosopis cinerea Warncke, 1992, syn. nov.), Hylaeus ferghanicus Morawitz, 1876 (= H. kuhlmanni Dathe, 2010, syn. nov.) and Hylaeus punctiventris Morawitz, 1876 (= H. atrocallosus Morawitz, 1893, syn. nov.). Hylaeus (Nesoprosopis) alexandrinus (Warncke, 1992) and Hylaeus (Prosopis) stellatus (Warncke, 1992) are introduced as new combinations.—Keys to most species known from Central Asia are provided.